Trends in risk taking and risk reduction among German MSM: Results of follow-up surveys Gay men and AIDS 1991 - 2007 - Axel J. Schmidt; Michael Bochow (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
Objectives: To calculate estimates for group level trends among German men who have sex with men (MSM) regarding parameters related to HIV epidemiology: frequency of anal intercourse, consistency in condom use, risk-taking, numbers of sex partners, incident bacterial STIs, and HIV-testing behaviour. Methods: Data derived from six large cross-sectional national follow-up surveys among MSM, conducted between 1991 and 2007. Questionnaires were circulated with German magazines for gay men; in 2003/2007, online recruitment was added. 23,878 anonymously self-administered questionnaires were analyzed in multiple regression models for five subgroups. Results: With the normalization of AIDS, restriction of anal intercourse to primary partnerships has lost its relevance as a risk avoidance strategy for MSM. Other traditional risk reduction strategies among MSM in Germany showed a high degree of time stability: Between 1991 and 2007, condom use in anal intercourse has been relatively stable; numbers of sex partners have been rather constant. No positive trends in the use of Nitrite inhalants were seen, party drugs were increasingly used by a minority of gay men during the 1990s. The syphilis epidemic seen after 1999 among German gay men is well reflected in the survey data. No evidence was found for a concurrent rise in urethral gonorrhoea. The proportion of MSM with a recent HIV test has been continuously increasing. Conclusions: We found no evidence for increasing 'carelessness' or 'prevention fatigue'. However, given the increasing proportions of MSM who frequently engage in anal intercourse with casual partners, a rise in HIV incidence is likely; especially if accompanied by a syphilis epidemic. Time trend analyses of these large behavioural follow-up surveys suggest that the rise in new HIV diagnoses among MSM in Germany may partially reflect an increased uptake of HIVtesting, rather than new infections due to the erosion of condom use or increased numbers of sex partners. – – Hintergrund: In vielen europäischen Ländern hat die Zahl der HIV-Neudiagnosen in den letzten Jahren zugenommen. In Deutschland konnte ein solcher Trend beobachtet werden für die Gruppe der Männer, die Sex mit Männern haben (MSM). Während die Zahl der HIV-Neudiagnosen, die vom Robert-Koch-Institut ausgewiesen wird, sich in den Jahren 1993 bis 2000 bei etwa 700 Fällen jährlich bewegte, stieg diese Zahl auf 1.540 im Jahr 2007. Häufig werden die steigenden HIV-Neudiagnosen in dieser Gruppe mit einer zunehmenden Sorglosigkeit erklärt, die zu einer Abnahme der Kondomverwendung beim Analverkehr führe. Empirische Daten für eine solche Deutung lagen jedoch bislang nicht vor. Tatsächlich ist weitgehend unklar, ob und in welchem Ausmaß die Zunahme der HIVNeudiagnosen auf einer Änderung des Testverhaltens in dieser Gruppe beruht (wie es beispielsweise für Großbritannien gezeigt werden konnte), oder ob sich immer mehr schwule und bisexuelle Männer mit HIV infiziert haben. Dieser Bericht stellt die deutschsprachige Kurzfassung einer derzeit zur Publikation eingereichten umfassenderen Analyse dar.
Keywords: 330